MAQASYID SYARI’AH PERSPEKTIF PEMIKIRAN IMAM SYATIBI DALAM KITAB AL-MUWAFAQAT - Abdurrahman Kasdi (Program Studi Hukum Keluarga Islam, 2014)
AllahrevealedIslamiclawisnothingelsethantotakethemaslaha(benefit)and avoidevils(jalbulmashalihwadar’ulmafasid).Inanotherword,Godsetlegal rulesforthebenefitofthehumanthemselves.ImamSyathibi dividedmaslaha tothreeimportantpartsi.e. dharuriyyat(primary),hajiyyat(secondary)and tahsinat(tertiary).MaqashidShariaissomethingthatmustexistinorder toaccomplishthebenefitofreligionandtheworld. Otherwise,itwillcause damageandevenlossoflifeandlivingsuchaseating,drinking,praying, fastingandotheractsofworship.Whatincludesbeneficiariesormaqashid Shariaharefive,namely:religion(al-din),soul(al-nafs),descent(an-nasl), property(al-mal)andaqal(al-aql).Thewaytokeepthelastfivecanbereached intwoways:intermsoftheirform(minnahiyyati al-wujud)bywayofkeeping andmaintainingaspectsperpetuatetheexistenceandtermsofnon-existance (min nahiyyati al ‘adam) by preventing the things that led to its absence.AllahrevealedIslamiclawisnothingelsethantotakethemaslaha(benefit)andavoidevils(jalbulmashalihwadar’ulmafasid).Inanotherword,Godsetlegalrulesforthebenefitofthehumanthemselves.ImamSyathibidividedmaslahatothreeimportantpartsi.e.dharuriyyat(primary),hajiyyat(secondary)andtahsinat(tertiary).MaqashidShariaissomethingthatmustexistinordertoaccomplishthebenefitofreligionandtheworld.Otherwise,itwillcausedamageandevenlossoflifeandlivingsuchaseating,drinking,praying,fastingandotheractsofworship.WhatincludesbeneficiariesormaqashidShariaharefive,namely:religion(al-din),soul(al-nafs),descent(an-nasl),property(al-mal)andaqal(al-aql).Thewaytokeepthelastfivecanbereachedintwoways:intermsoftheirform(minnahiyyatial-wujud)bywayofkeepingandmaintainingaspectsperpetuatetheexistenceandtermsofnon-existance(min nahiyyati al ‘adam) by preventing the things that led to its absence.